2020
DOI: 10.1002/fsn3.1547
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ultrasound technology to break seed dormancy of common lambsquarters (Chenopodium album)

Abstract: Although seed dormancy is advantageous for annual plants in the wild, unsynchronized germination in the laboratory leads to increased error in measurements. Therefore, techniques to promote and synchronize germination are routinely used. Ultrasound is one of the newest methods for breaking dormancy in weed seeds. We have investigated whether ultrasonic waves can be used to break seed dormancy of common lambsquarters (Chenopodium album), a highly competitive annual weed that leads to significant reduction of yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…Our data show that pretreating seeds with ultrasound effectively promoted germination percentage and rate (Figure 1, Table 2). This finding is consistent with previous studies in other species that have utilized ultrasound to promote seed germination (Babaei-Ghaghelestany et al, 2020;Ding et al, 2018;Kratovalieva et al, 2012;Miano et al, 2015;Rifna et al, 2019). For example, Ding Ultrasound treatments are believed to induce changes in the seed coat, facilitating influx or efflux of water and mineral elements into cells (Miano et al, 2015;Qin et al, 2012) and/or to increase the activity of alpha-amylase enzyme and therefore the rate of starch metabolism (Yaldagard et al, 2007(Yaldagard et al, , 2008.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our data show that pretreating seeds with ultrasound effectively promoted germination percentage and rate (Figure 1, Table 2). This finding is consistent with previous studies in other species that have utilized ultrasound to promote seed germination (Babaei-Ghaghelestany et al, 2020;Ding et al, 2018;Kratovalieva et al, 2012;Miano et al, 2015;Rifna et al, 2019). For example, Ding Ultrasound treatments are believed to induce changes in the seed coat, facilitating influx or efflux of water and mineral elements into cells (Miano et al, 2015;Qin et al, 2012) and/or to increase the activity of alpha-amylase enzyme and therefore the rate of starch metabolism (Yaldagard et al, 2007(Yaldagard et al, , 2008.…”
Section: Discussionsupporting
confidence: 91%
“…To evaluate the efficacy of ultrasound treatment, we used methods developed by Babaei‐Ghaghelestany et al. ( 2020 ). Redroot pigweed seeds were exposed to ultrasonic waves for 10, 20, 30, and 40 min to evaluate this treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in the same species showed that sonication (20 kHz and 350 W) for 5 min stimulated seedlings but was less efficient than thermal scarification in terms of GP and germination rate index (GRI) 96 . Furthermore, the germination of other dormant seeds, including orchid ( Calanthe discolor ) 60 and lamb's quarters ( Chenopodium album ) 54 were also positively affected by different ultrasound systems. Contrarily, sonication treatment failed to stimulate the germination of dormant seeds of Xylopia emarginata 95 …”
Section: Unveiling the Impact Of Ultrasound In Overcoming Seed Dorman...mentioning
confidence: 99%
“…Many studies have tried to improve caper seed germination and to break the possible physical dormancy with different types of scarifications (mechanical, chemical, thermal or biological) [5][6][7][8] and to break the physiological dormancy with the use of gibberellic acid (GA 3 ) and potassium nitrate [9][10][11][12]. The ultrasound application has been used in seed germination studies of both cultivated plants and weeds [13][14][15][16][17][18], but it is one of the least-studied methodologies in caper seeds.…”
Section: Introductionmentioning
confidence: 99%